Practical postexercise recovery strategies in male adult professional soccer players : A systematic review - Ribeiro, J.; Sarmento, H.; Silva, A. F.; Clemente, F. M. (Strength and Conditioning Journal, 2021)
The aim of this article was to systematically review and provide practical recommendations, where possible, for recovery strategies that are currently in use in soccer-specific practices among adult male professional players. A systematic search was conducted according to PRISMA guidelines on Web of Science, SPORTdiscus, Scopus, and PubMed databases. The effects of cold-based recovery techniques on performance recovery and attenuating the muscle soreness were evident. Complementarily, some evidence was found that favors foam rolling and massage and compression garments. The active recovery and electronic recovery instruments presented little evidence supporting their usefulness in accelerating the recovery process of soccer players.